2018
DOI: 10.5194/amt-11-1009-2018
|View full text |Cite
|
Sign up to set email alerts
|

Importance of interpolation and coincidence errors in data fusion

Abstract: Abstract. The complete data fusion (CDF) method is applied to ozone profiles obtained from simulated measurements in the ultraviolet and in the thermal infrared in the framework of the Sentinel 4 mission of the Copernicus programme. We observe that the quality of the fused products is degraded when the fusing profiles are either retrieved on different vertical grids or referred to different true profiles. To address this shortcoming, a generalization of the complete data fusion method, which takes into account… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Furthermore, other assumptions and inaccuracies in the observation operator (which transforms the model state into the observation space) also contribute to the representativeness error. Ceccherini et al (2018) showed the importance of interpolation and coincidence errors for retrievals on different vertical grids in data fusion. For example, the difference in the 5 layers between the retrieval grid and the MOCAGE CTM may easily lead to regridding (interpolation) errors that may make it difficult to assimilate stratospheric (high concentration) and tropospheric ozone (low concentration) together.…”
Section: Satellite Observations Error Covariance Matrixmentioning
confidence: 99%
“…Furthermore, other assumptions and inaccuracies in the observation operator (which transforms the model state into the observation space) also contribute to the representativeness error. Ceccherini et al (2018) showed the importance of interpolation and coincidence errors for retrievals on different vertical grids in data fusion. For example, the difference in the 5 layers between the retrieval grid and the MOCAGE CTM may easily lead to regridding (interpolation) errors that may make it difficult to assimilate stratospheric (high concentration) and tropospheric ozone (low concentration) together.…”
Section: Satellite Observations Error Covariance Matrixmentioning
confidence: 99%
“…Carried out in the context of several satellite validation studies (for Sentinel-5P, the European Space Agency's Climate Change Initiative, and the Satellite Application Facility on Atmospheric Composition Monitoring) and considering the exploration of advanced data fusion methods (Cortesi et al, 2018), with a view to harmonize practices across satellite missions and Earth Observation domains, this work is meant to provide an overview of existing approaches that allow estimating and potentially (partially) correcting for these observational differences in quantitative data comparisons. The uncertainties that are tied to these differences, as typically expressed in terms of covariance matrices, as a result are also (partially) removed from the uncertainty budget of the data comparison.…”
Section: Introductionmentioning
confidence: 99%
“…The CDF method was proved (Ceccherini, 2016) to be equivalent to the measurement space solution data fusion method (Ceccherini et al, 2009) and the latter was successfully applied to the data fusion of MIPAS-ENVISAT and IASI-METOP measurements (Ceccherini et al, 2010a, b) and of MIPAS-STR and MARSCHALS measurements (Cortesi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, as highlighted in Ceccherini et al (2018), the CDF provides poor results when applied to inconsistent measurements. Three causes of inconsistency are possible:…”
Section: Introductionmentioning
confidence: 99%